2012
DOI: 10.21273/hortsci.47.6.704
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Seaweed Extract-induced Transcriptome Leads to Identification of a Negative Regulator of Salt Tolerance in Arabidopsis

Abstract: Successful development of plants resistant to salinity stress is problematic as a result of the complex polygenic natures of salt tolerance. Previously, alkaline extracts of the brown seaweed Ascophyllum nodosum have shown promise in enhancing plant tolerance toward abiotic stresses. To understand the underlying molecular mechanisms, the whole genome transcriptome of Arabidopsis undergoing salt stress was analyzed by microarray analysis after treatment with the chemical compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…They found that salt stress significantly increases PME31 expression and also reported that the knockdown mutant pme31 displayed a hypersensitive phenotype to salt stress in seed germination and post-germination growth with lower expression of several salinity stress-related genes (DREB2A, RD29A and RD29B). An Arabidopsis mutant with reduced expression of a PMEI gene (At1g62760) exhibited reduced sensitivity to salt stress [111]. Phenotypes like enhancement of root growth, increase of fresh weight, and appearance of less chlorosis and necrosis in NaCl treatments in the pmei mutant, suggested that PMEI works as a negative regulator of salinity tolerance.…”
Section: Cell Wall Remodeling Under Salinity Stressmentioning
confidence: 99%
“…They found that salt stress significantly increases PME31 expression and also reported that the knockdown mutant pme31 displayed a hypersensitive phenotype to salt stress in seed germination and post-germination growth with lower expression of several salinity stress-related genes (DREB2A, RD29A and RD29B). An Arabidopsis mutant with reduced expression of a PMEI gene (At1g62760) exhibited reduced sensitivity to salt stress [111]. Phenotypes like enhancement of root growth, increase of fresh weight, and appearance of less chlorosis and necrosis in NaCl treatments in the pmei mutant, suggested that PMEI works as a negative regulator of salinity tolerance.…”
Section: Cell Wall Remodeling Under Salinity Stressmentioning
confidence: 99%
“…Based on undisclosed results of a microarray analysis of Arabidopsis Col-0 plants subjected to 125 mM NaCl in the presence or absence of the organic fraction of an alkaline ANE, genes not previously linked to salinity stress tolerance, of which the expression was downregulated in the presence of ANEs, were functionally analyzed by means of knockout mutants. As such, At1g62760, encoding a putative pectin methylesterase inhibitor, was identified as a novel negative regulator of salt tolerance (Jithesh et al 2012). In a subsequent study, 2-week-old Arabidopsis Col-0 plants subjected to 100 and 150 mM NaCl for 24 h were treated with a 1 g L −1 equivalent of a methanolic ANE fraction (MEA) (Jithesh et al 2018).…”
Section: Molecular Analysis Of Ane-induced Salinity Stress Tolerance mentioning
confidence: 99%
“…At the physiological level, these extracts have been found to influence hormones levels that, in turn, influence physiological processes even at very low concentrations (Wally et al, 2013). They impact plant-signalling mechanisms through a multitude of plant processes and cellular modifications including osmotic/oxidative stresses such as salinity, freezing and drought stress (Jithesh et al, 2012). Contrary to the effects of ANE on plant development, the effect of seaweed extracts on the biology of the rhizosphere is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%